2009
DOI: 10.1111/j.1365-2052.2008.01804.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci for clinical–chemical traits in swine

Abstract: Clinical-chemical traits are diagnostic parameters essential for characterization of health and disease in veterinary practice. The traits show significant variability and are under genetic control, but little is known about the fundamental genetic architecture of this variability, especially in swine. We have identified QTL for alkaline phosphatase (ALP), lactate (LAC), bilirubin (BIL), creatinine (CRE) and ionized sodium (Na(+)), potassium (K(+)) and calcium (Ca(++)) from the serum of 139 F(2) pigs from a Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
(57 reference statements)
1
15
0
Order By: Relevance
“…Studies carried out on pigs, based on F 2 intercrosses between Pietrain and Meishan and between Landrace and Korean native pigs respectively, reported several QTL for serum Ca 2+ level on four porcine chromosomes (SSC), SSC6, SSC13, SSC14 and SSC18 (Reiner et al . ; Yoo et al . ).…”
Section: Significant (False Discovery Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out on pigs, based on F 2 intercrosses between Pietrain and Meishan and between Landrace and Korean native pigs respectively, reported several QTL for serum Ca 2+ level on four porcine chromosomes (SSC), SSC6, SSC13, SSC14 and SSC18 (Reiner et al . ; Yoo et al . ).…”
Section: Significant (False Discovery Ratementioning
confidence: 99%
“…All these results on SSC13 are in agreement with the confidence interval of a QTL for serum Ca 2+ level reported by Reiner et al . () but may exclude an important role of the calcium‐sensing receptor gene ( CASR ) in affecting this clinical–chemical trait in the investigated pig population. CASR (positioned on SSC13:147 907 932–147 935 070) is one of the main genes whose variability influences the level of this electrolyte in human serum (Kapur et al .…”
Section: Significant (False Discovery Ratementioning
confidence: 99%
“…Elevated Crea levels occur in conditions that decrease the glomerular filtration (45). The synaptotagmin-1 (SYT1) gene is located in the QTL region in SSC5 for Crea and the orthologous region on HSA 12.…”
Section: Single Qtl Analysismentioning
confidence: 99%
“…However, studies on QTL for clinical-chemical traits other than lipid levels are still scarce when it comes to pigs. So far one study addressed QTL for clinical-chemical traits other than lipid levels using an F 2 intercross between Pietrain and Meishan pigs (45). As for QTL analysis of serum lipid levels, Gallardo et al (23, half-sib Duroc population), Chen et al (10, F 2 intercross between White Duroc and Erhualian pigs), and Uddin et al (53, F 2 intercross between Duroc and Pietrain pigs) reported QTL for blood lipid levels.…”
mentioning
confidence: 97%
“…The CC homozygotes had thinner backfat for all three calculating points, respectively. However, the marbling scores, which reflect the levels of Several quantitative trait loci (QTL) for meat quality traits including backfat and total body fat (Rohrer, 2000;Edwards et al, 2008) and physiological traits in blood such as alkaline phosphatase activity (Yoo et al, 2012), CD4positive leukocyte number (Wattrang et al, 2005), and bilirubin levels (Reiner et al, 2008) (www.animalgenome.org/ cgi-bin/QTLdb) are mapped at the region on Sus scrofa chromosome 8 (SSC8) where SETD7 is located. Reports of an F 2 population of an intercross between Large White and Chinese Meishan pigs described a significant difference in the levels of backfat thickness (Xu et al, 2007), marbling score, and intramuscular fat percentage (Xu et al, 2005), according to the SETD7 genotypes.…”
Section: Resultsmentioning
confidence: 99%